Reclamation and agricultural reuse of wastewater: the experience of Cagliari sewage treatment plant (Sardinia - Italy) - Vacca S.; Botti P.; Coppola A.; Meloni B. (Food security under water scarcity in the Middle East: Problems and solutions, 2005)
In Sardinia, like in many other Mediterranean regions, the recurrent droughts and climate change have dramatically reduced the available water resources. As a result of this critical situation, in 1995 the Italian Government declared a state of emergency and drew up a programme for financial provision by the State and local government authorities with the aim to reduce such a serious deficit. One of the actions has been focused on reclaiming and reusing the effluent coming from the sewage treatment plant of Cagliari. In the present work the multidisciplinary research preliminarily carried out by the Ente Autonomo del Flumendosa (EAF - Sardinia - Italy) to evaluate the suitability of Is Arenas effluent in irrigation is illustrated.
LNCV [Landau Network-Centro Volta] International Forum: Food Security under Water Scarcity in the Middle East: Problems and Solutions, 24-27 Nov 2004, Como (Italy)